Solubilization and Interactions of Thiram with Surfactants: Micellar Effects on Adsorption Characteristics of Thiram onto Activated Carbon - GÖKTÜRK, SİNEM (TAYLOR & FRANCIS INC, 2015)
The solubilization of thiram was studied in micellar solutions of two surfactants possessing the same hydrocarbon tail but different hydrophilic head groups, namely sodium dodecyl sulfate and dodecyltrimethylammonium bromide. Conductivity, spectrophotometry, and surface tension measurements have been used in quantitative analysis of the interaction between thiram and surfactants. In this work the adsorption of thiram onto selected two different activated carbons has been also studied in the absence and presence of micelles. The interaction of thiram in different micellar solutions provided information about the characteristics of adsorption properties of poorly soluble pesticide thiram onto activated carbon in the presence of micelles.
Keywords: Adsorption; pesticide; solubilization; surfactant; thiram; DESORPTION; REMOVAL; DYE